ANALYSIS OF LITERATION MOVEMENT IN STUDENTS OF SDN 1 BIAU BUOL DISTRICT - Firmansyah B. Hi. Majo; Rizal Rizal (Universitas Tadulako, 2020)
This research aims to; 1) Describe the obstacles faced in the implementation of the School Literacy Movement at SDN 1 Biau. 2) Describe the Obstacles encountered in the implementation of the School Literacy Movement (GLS) at SDN 1 Biau. 3) Describe efforts to overcome obstacles in the implementation of the School Literacy Movement (GLS) SDN 1 Biau. This research uses qualitative research type. Qualitative research is a research method used to examine natural conditions of objects. At the habituation stage there are a number of indicators that have been fulfilled such as the 15-minute reading activity that is carried out at the beginning, middle, or the end of the lesson and has a reading angle that functions to attract students' interest in reading as well as students are expected to be close to the source of literacy. Good book reading strategies. The literacy movement at school is going well. This is based on the results of student questionnaires in the literacy movement at SDN 1 Biau from the number of 20 student respondents that can be seen from the percentage of answers always at 16.13%, while 34.31% answers frequently, 28.18 answers sometimes 14.31 % answered rarely and 7.07 answered never. So based on these data it can be concluded from several available alternative indicators. Students prefer to answer frequently and at least answer never. This means that the literacy movement at SD 1 Biau has gone well as expected by all parties.